Ranah Graduation dalam Sistem Appraisal yang Digunakan pada Harian Bali Post dan Tribun Bali - Putri, Ida Ayu Suryantini (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 26 No 2 (2019): SeptemberDO - 10.24843/ling.2019.v26.i02.p05, 2019)
Abstract : This article focus on the use of one part of appraisal system that is graduation. Data were colected from Daily Newspaper Bali Post and Tribun Bali, criminal news in particular. The author used note technique and the method of observing. The collected data then were analized using appraisal system by White and finding the percentage to get the number of appearance and comparation. According to the result of analisys, it can be seen that the device graduation of each reporters are different, depending on the incidents that occur and the situation    Keywords :     Appraisal, graduation , criminal news.